PERANCANGAN UI/UX APLIKASI UMKM DENGAN METODE DESIGN THINKING MENGGUNAKAN FIGMA - Susi Widayati; Kokoy Rokoyah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The design of the User Interface and User Experience using the Design Thinking method with the help of Figma in the Dapoer Ibu business aims to improve comfort, efficiency, and security for users through the development of applications that are easier to use and more effective. The Design Thinking method is applied to understand user needs in more depth, evaluate user assumptions, and reformulate existing problems so that various alternative strategies and solutions can be found that may not have been previously seen. In this design process, Figma is used as a design tool to produce a more optimal and attractive mobile application display for users